2015
DOI: 10.15436/2376-0494.15.024
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD Susceptibility Genes and Their Association with Type 2 Diabetes and Obesity in a New Mexico Population

Abstract: Objective Genome-wide association studies have identified single-nucleotide polymorphisms (SNPs) that increase the risk of developing non-alcoholic fatty liver disease (NAFLD). One purpose of this study was to determine the frequencies of NAFLD susceptibility SNPs in a non-Hispanic white and Hispanic population who attended a clinic in northeast Albuquerque, NM. Another goal was to determine associations with selected indicators in this New Mexican population. Methods This cohort study involving 168 voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…[18,2022] Certain studies pointed out the fact that PNPLA3 gene increases hepatic steatosis by hindering TG decrease. [23] The variant allele of PNPLA3 rs738409 gene polymorphisms might contribute to the increase of AST and ALT, being correlated with age, gender, BMI and type 2 DM [57,58] in GG homozygotes of this SNP. Moreover, the same gene polymorphism seems to be involved in the development of non-alcoholic steatohepatitis (NASH) or type 1 DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,2022] Certain studies pointed out the fact that PNPLA3 gene increases hepatic steatosis by hindering TG decrease. [23] The variant allele of PNPLA3 rs738409 gene polymorphisms might contribute to the increase of AST and ALT, being correlated with age, gender, BMI and type 2 DM [57,58] in GG homozygotes of this SNP. Moreover, the same gene polymorphism seems to be involved in the development of non-alcoholic steatohepatitis (NASH) or type 1 DM.…”
Section: Discussionmentioning
confidence: 99%
“…[18,2022] Garner underlined that homozygotes of the ancestral (C) allele of PNPLA3 rs738409 leads to a decrease of triglycerides (TG) in the liver, it's variant polymorphism increasing hepatic steatosis through the prevention of TG decrease. [23] Moreover, it seems that PNPLA3 rs738409 gene polymorphism is related to obesity and elevated levels of transaminases in teenagers suggesting that the early detection of its variant allele might be useful in the prevention of these disorders through a healthy and rigorous lifestyle. [24]…”
Section: Introductionmentioning
confidence: 99%
“…The PEMT pathway, as represented within our studies, is necessary when cells lack an external supply to choline for the Kennedy pathway, which is the main source for PE and PC biosynthesis in mammals (Vance 2014). PEMT is low in most tissues with the exception of the liver and it has been reported that diabetic patients have significantly increased PEMT levels (Garner 2015).…”
Section: Characterizing the Role Of Agpat1/slc1 Lipotoxicity Suppress...mentioning
confidence: 54%
“…Metabolic diseases have been linked to genetic risk factors, with many genome-wide association (GWAS) studies providing single-nucleotide-polymorphism (SNP) associations with metabolic disease causing loci (Garner 2015). But the significant down-side to GWAS studies is the inability to determine if the mapped SNPs are associated with the underlying causal gene (Woo et al 2018), and many diseases are polygenic so single gene association studies become insufficient.…”
Section: Genetic Interaction Network (Gin) Analysismentioning
confidence: 99%